Antioxidant and Cytotoxic Activity of Phellinus Mushrooms from Northeast Thailand - Sonesay Thammavong*; Methin Phadungkit; Pornpun Laovachirasuwan; Khwanyuruan Naksuwankul; Waraporn Saentaweesuk; Atit Silsirivanit; Sopit Wongkham (Iranian Society of Pharmacognosy, 2021)
Background and objectives: Phellinus belongs to the family of Hymenochaetaceae. In Traditional Chinese Medicine, it has been used as an ingredient for the treatment of different types of cancer, ischemia and skin diseases for thousands of years. The present study was aimed to evaluate and compare the mushroom constituents (total phenolic and flavonoid contents) and antioxidant and cytotoxic effect against cholangiocarcinoma cells. Methods: The samples of Phellinus mushrooms including P. igniarius, P.lineteus and P.nigricans were prepared in two ways: macerated in 95% ethanol and decocted in distilled water. The antioxidant activity of the six  extracts were evaluated using the DPPH, ABTS and FRAP assays. Total phenolics and flavonoids were determined using colorimetric tests. In addition, cytotoxic activities against cholangiocarcinoma cell lines (KKU-100 & KKU213A) were assessed by the SRB assay. Results: All ethanol extracts of samples showed significantly stronger antioxidant activity compared to aqueous extracts (p <0.05), while the ethanol extracts contained higher total phenolic and flavonoid contents. Phellinus linteus showed the highest antioxidant activity and total phenolic content when compared to P. igniarius and P. nigricans. All samples showed high cytotoxicity against cholangiocarcinoma cell lines, particularly the ethanol extract of P. linteus. The cytotoxicity was correlated to the phytochemical contents and antioxidant activity of each Phellinus mushroom.  Conclusions: The cytotoxicity and antioxidant activity are in proportion to the phenolic and flavonoid contents. Therefore, the antioxidant capacity of the mushroom extracts may advocate anti-cancer effects.